2014
DOI: 10.1007/s11665-014-1373-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Premixed Al-Cu Powder on the Stir Zone in Friction Stir Welding of AA3003-H18

Abstract: In this research, 3-mm-thick AA3003-H18 non-heat-treatable aluminum alloy plates were joined by friction stir welding (FSW). It was performed by adding pure Cu and premixed Cu-Al powders at various rotational speeds of 800, 1000, and 1200 rpm and constant traveling speeds of 100 mm/min. At first, the powder was filled into the gap (0.2 or 0.4 mm) between two aluminum alloy plates, and then the FSW process was performed in two passes. The microstructure, mechanical properties, and formation of intermetallic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The additions of various reinforcement particles have been introduced as an improvement strategy for increasing the mechanical properties of FSWed joints of strain-hardened Al alloys. For instance, the effects of TiC [162], TiO 2 [163], and SiC [164] nanoparticles, Cu and pre-mixed Cu-Al Powder [56,165], Al 3 Sc compound [166], and inserting Cu foils [167] on the mechanical properties of FSWed joints of Al alloys have been previously investigated. All of these studies have unanimously reported that the incorporation of reinforcement particles into the gap between two sheets strengthens the stir zone's mechanical properties, provided that appropriate welding parameters are chosen.…”
Section: Incorporation Of Reinforcement Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The additions of various reinforcement particles have been introduced as an improvement strategy for increasing the mechanical properties of FSWed joints of strain-hardened Al alloys. For instance, the effects of TiC [162], TiO 2 [163], and SiC [164] nanoparticles, Cu and pre-mixed Cu-Al Powder [56,165], Al 3 Sc compound [166], and inserting Cu foils [167] on the mechanical properties of FSWed joints of Al alloys have been previously investigated. All of these studies have unanimously reported that the incorporation of reinforcement particles into the gap between two sheets strengthens the stir zone's mechanical properties, provided that appropriate welding parameters are chosen.…”
Section: Incorporation Of Reinforcement Particlesmentioning
confidence: 99%
“…Rotational and traverse speeds, the number of FSW passes, and the direction of the multi-passes are the most common variables that have been studied on FSW nonheat-treatable Al alloys with the addition of reinforcement particles. Subsequently, the significant effects of these parameters on mechanical properties (hardness, tensile strength, and fatigue) have been well documented [56,162,165,168].…”
Section: Incorporation Of Reinforcement Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers [7][8][9][10][11][12][13] have conducted experimental studies to predict the effect of interlayers on the mechanical properties of FSW joints. Interlayers of Zinc (Zn), Copper (Cu), Brass, Aluminium, Silicon carbide (SiC), Titanium Carbide (TiC) etc, are used to improve the mechanical properties of FSW joints.…”
Section: Introductionmentioning
confidence: 99%
“…The joints fabricated using a 10 μm thickness of Zn interlayer possessed a higher tensile strength than the FSW joint produced with different Zn interlayers. Abnar et al [9,10] used pure Cu and a mixture Al-Cu particles as interlayers in FSW of AA3003 aluminium alloy. In this experimental study, the interlayer particles are first fused into the gap of abutting plates using friction stir processing, and the FSW process is performed afterwards.…”
Section: Introductionmentioning
confidence: 99%